2017
DOI: 10.1017/cjn.2016.426
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Therapy for Apathy in Alzheimer’s Disease: A Systematic Review and Meta-Analysis

Abstract: The lack of an effect could be explained by methodological limitations, publication bias, and heterogeneity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 87 publications
0
20
0
Order By: Relevance
“…A comprehensive meta-analysis of the reported pharmacological studies [ 42 ] provides little evidence for their effectiveness in treating apathy in AD, although it did not have access to the most recent methylphenidate data. The findings are likely to have been affected by the small number of studies, and heterogeneity in drugs, sample and apathy assessment.…”
Section: Treatmentmentioning
confidence: 99%
“…A comprehensive meta-analysis of the reported pharmacological studies [ 42 ] provides little evidence for their effectiveness in treating apathy in AD, although it did not have access to the most recent methylphenidate data. The findings are likely to have been affected by the small number of studies, and heterogeneity in drugs, sample and apathy assessment.…”
Section: Treatmentmentioning
confidence: 99%
“…reported in a post hoc analysis of a placebo-controlled RCT that apathy in patients with more severe AD was significantly improved after 24-week treatment of donepezil, as a secondary outcome [33]. Nonetheless, a meta-analysis revealed that pharmacological therapy using ChEI, memantine, and psycho-stimulants including methylphenidate had no significant effect on apathy [34].…”
Section: Discussionmentioning
confidence: 99%
“…One recent article from January 2017 reviewed recent pharmacological and non-pharmacological approaches for the management of apathy in AD (Theleritis et al, 2017) and reported the potential interest of cholinesterase inhibitors (ChEIs), methylphenidate and gingko biloba in reducing levels of apathy, whereas Sepehry et al's review did not reveal any significant treatment effect likely to reduce apathy in AD (Sepehry et al, 2017). In Theleritis, among 6 studies using galantamine (4 RCT and 2 open-label studies), five studies did show an improvement of apathy levels after treatment.…”
Section: Reviews and Meta-analysesmentioning
confidence: 99%